Ammonia Production by Streptomyces Symbionts of Acromyrmex Leaf-Cutting Ants Strongly Inhibits the Fungal Pathogen Escovopsis - Basanta Dhodary; Dieter Spiteller (Microorganisms, 2021)
Leaf-cutting ants live in mutualistic symbiosis with their garden fungus Leucoagaricus gongylophorus that can be attacked by the specialized pathogenic fungus Escovopsis. Actinomyces symbionts from Acromyrmex leaf-cutting ants contribute to protect L. gongylophorus against pathogens. The symbiont Streptomyces sp. Av25_4 exhibited strong activity against Escovopsis weberi in co-cultivation assays. Experiments physically separating E. weberi and Streptomyces sp. Av25_4 allowing only exchange of volatiles revealed that Streptomyces sp. Av25_4 produces a volatile antifungal. Volatile compounds from Streptomyces sp. Av25_4 were collected by closed loop stripping. Analysis by NMR revealed that Streptomyces sp. Av25_4 overproduces ammonia (up to 8 mM) which completely inhibited the growth of E. weberi due to its strong basic pH. Additionally, other symbionts from different Acromyrmex ants inhibited E. weberi by production of ammonia. The waste of ca. one third of Acomyrmex and Atta leaf-cutting ant colonies was strongly basic due to ammonia (up to ca. 8 mM) suggesting its role in nest hygiene. Not only complex and metabolically costly secondary metabolites, such as polyketides, but simple ammonia released by symbionts of leaf-cutting ants can contribute to control the growth of Escovopsis that is sensitive to ammonia in contrast to the garden fungus L. gongylophorus.